2014
DOI: 10.2355/isijinternational.54.2926
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbon Bainite Steel with High Strength and Toughness Processed by Recrystallization Controlled Rolling and Ultra Fast Cooling (RCR+UFC)

Abstract: Effects of temperature, strain, strain rate and cooling rate on austenite grain size were investigated at first. The results show that by increasing the strain from 0.0 to 0.5 can significantly refine austenite grains for different deformation temperatures studied. However, by increasing the strain from 0.5 to 0.8 can not continue to refine austenite grains for higher deformation temperatures of 1 100 and 1 150°C, while austenite grains can be further refined for lower deformation temperature of 1 000°C. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As shown in Fig.4, the A-E curve was obtained by using the A-E equation, which was provided by equation (2). The A-E of the adjusting valve has a nonlinear relationship with the opening rate of the adjusting valve.…”
Section: Definition Of Adjusting-efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig.4, the A-E curve was obtained by using the A-E equation, which was provided by equation (2). The A-E of the adjusting valve has a nonlinear relationship with the opening rate of the adjusting valve.…”
Section: Definition Of Adjusting-efficiencymentioning
confidence: 99%
“…The thermo-metallurgical phase transformations of the steel take place during the cooling process on the run-out table (ROT). The microstructure and mechanical properties of steel are directly related to the cooling process [1][2][3][4]. Ultra-fast cooling(UFC) can provide flexible cooling paths in order to achieve the desirable phase transformations, which makes it an appealing selection for the cooling line after rolling [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…5,18) Besides finish rolling temperature, cooling rate after hot rolling also significantly influences grain size and precipitation behavior, and ultra fast cooling (UFC) technology is used to obtained higher strength steel. 19,20) Compared with the normal cooling after hot rolling, UFC can effectively suppress the growth of austenite grain and refine the size of ferrite grain and precipitation. Tang et al 20) reported that the yield strength of hot rolled microalloyed steels can be increased by more than 100 MPa by using UFC over conventional accelerated cooling, which is associated with grain refinement and precipitation.…”
Section: Microstructural Characteristics With Various Finish Rolling mentioning
confidence: 99%
“…Extensive efforts have been made on optimizing the microstructure and mechanical properties of alloy steels by controlling cooling. [17][18][19] However, the studies on controlling cooling after hot rolling of duplex low-density steels are still rarely reported. In the present work, different cooling rates were adopted in a low-density duplex steel after hot rolling for investigating the relevant influencing mechanism.…”
Section: Introductionmentioning
confidence: 99%